1997
DOI: 10.5254/1.3538419
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Conductivity of Polystyrene-Rubber Blends Loaded with Carbon Black

Abstract: Polystyrene/rubber blends have been loaded with carbon black (CB) and the filler localization in the two-phase polyblends has been studied in relation to the chemical structure of the rubber. The CB localization and the electrical conductivity are greatly influenced by the substitution of the rubber chains. In polystyrene/polybutadiene blends, the filler is localized within the polybutadiene phase. In contrast, in polystyrene/polyisoprene and polystyrene/ethylene—propylene rubber (EPM) blends, CB is mainly loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
3

Year Published

1999
1999
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 0 publications
0
17
0
3
Order By: Relevance
“…5,[15][16][17][18][19][20][21][22][23] The main advantage of these ternary systems is the relatively low CB content required to achieve percolation compared to conventional binary systems. It has been suggested that the lower ⌽ c values are due to multiple percolation effects, where a continuous network of conducting pathways is formed within the existing continuous network of the binary host.…”
Section: Introductionmentioning
confidence: 99%
“…5,[15][16][17][18][19][20][21][22][23] The main advantage of these ternary systems is the relatively low CB content required to achieve percolation compared to conventional binary systems. It has been suggested that the lower ⌽ c values are due to multiple percolation effects, where a continuous network of conducting pathways is formed within the existing continuous network of the binary host.…”
Section: Introductionmentioning
confidence: 99%
“…In a sense this is a form of double percolation where a continuous path is formed within an existing continuous path, with the former being conducting. 16,17,29,30,35,36 This term was ®rst used by Sumita and co-workers 29,30 in conducting blends to describe the heterogenous distribution of the conducting ®ller at the cocontinuous interface of an insulating binary host resulting in very low values of Φ c . In the case of SAN and CB, the double percolation occurred within a copolymer material.…”
Section: ±23mentioning
confidence: 99%
“…2,11,17,24,25,35,36 In most practical applications, processing of polymer components involves shear mixing in the molten state within an extruder, followed by some moulding process to obtain the ®nal product shape. In the case of conducting blends where the host polymer is mixed with ®llers, this can often lead to overdispersion of the ®ller, resulting in the loss of ®ller structure, or orientation effects of the blend which may alter Φ c .…”
Section: Effect Of Processing On the Critical Percolation Contentmentioning
confidence: 99%
“…Examples of this kind are the work by Geuskens et al in as early as 1987, 19 which shows that for the same carbon loading, the resistivity of the cocontinuous polymer/rubber blends is several orders of magnitude smaller than that of the single polymer/carbon black composites. Recent works on polymer/elastomer combinations 20,21 and on polymer/polymer systems [22][23][24][25][26][27][28][29] have also shown that the double percolation approach can produce conducting materials at a lower filler concentration. All of these studies suggest that polymer blends can be an interesting approach for making conductive polymers.…”
Section: Introductionmentioning
confidence: 99%